2020
DOI: 10.1111/ipd.12726
|View full text |Cite
|
Sign up to set email alerts
|

The effect of extraction of lower primary canines on the morphology of dental arch: A systematic review and meta‐analysis

Abstract: Background The beneficial effect of the extraction of primary canines in the resolution of incisor irregularity and its side effects are controversial. Aim To systematically review the effects of the extraction of primary canines in incisor irregularity and dental arch morphology. Design Controlled non‐randomized (non‐RCT) and randomized clinical trials (RCT) evaluating children treated with extraction of primary canines compared with those without intervention. Results A total of 984 articles were found, of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…In the study of adult patients with bimaxillary protrusion, Leonardi et al [17] found that the upper and lower lips were moved backward by 2 to 3.2 mm and 2 to 4.5 mm respectively after the extraction of the rst premolar, indicating that the rebuilding in soft tissue of the lips will occur with the movement of the teeth. Adults lack the ability to remodel soft tissue, suggesting that adult patients with thick lip can obtain better lip shape after tooth extraction, which is consistent with the research conclusions of some studies [18,19]. In addition, we also observed a decreased change in 1/3 face height and chin high and opposite in soft tissue angle in the extraction group, which might be that these cases were designed as moderate anchorage, and the molars move mesially, resulting in a counterclockwise rotation of the mandible [20,21].…”
Section: Discussionsupporting
confidence: 89%
“…In the study of adult patients with bimaxillary protrusion, Leonardi et al [17] found that the upper and lower lips were moved backward by 2 to 3.2 mm and 2 to 4.5 mm respectively after the extraction of the rst premolar, indicating that the rebuilding in soft tissue of the lips will occur with the movement of the teeth. Adults lack the ability to remodel soft tissue, suggesting that adult patients with thick lip can obtain better lip shape after tooth extraction, which is consistent with the research conclusions of some studies [18,19]. In addition, we also observed a decreased change in 1/3 face height and chin high and opposite in soft tissue angle in the extraction group, which might be that these cases were designed as moderate anchorage, and the molars move mesially, resulting in a counterclockwise rotation of the mandible [20,21].…”
Section: Discussionsupporting
confidence: 89%